Mathematical modeling of a one-dimensional demographic process (Моделювання, керування та інформаційні технології, 2020)
The specifics of the current stage of society connects with significant changes in directions and internal scales and interstate migration of the population. In this regard population migration processes between the two states are exploring in a one-dimensional case. Now the scientific literature offers different mathematical models of these processes [1]. However, we will use diffusion models for modeling these processes.